2016
DOI: 10.1016/j.cad.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary approach to the extraction of object construction trees from 3D point clouds

Abstract: In order to extract a construction tree from a finite set of points sampled on the surface of an object, we present an evolutionary algorithm that evolves set-theoretic expressions made of primitives fitted to the input point-set and modeling operations. To keep relatively simple trees, we use a penalty term in the objective function optimized by the evolutionary algorithm. We show with experiments successes but also limitations of this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…To be topologically consistent in the sense of 3D modelling, we treat overlapping similarly to Fayolle and Pasko [51]. We represent a constructive model using a binary (CSG) construction tree structure with primitive solids at the leaves and operations at the internal nodes of the tree.…”
Section: D Aggregation For Scene Modellingmentioning
confidence: 99%
“…To be topologically consistent in the sense of 3D modelling, we treat overlapping similarly to Fayolle and Pasko [51]. We represent a constructive model using a binary (CSG) construction tree structure with primitive solids at the leaves and operations at the internal nodes of the tree.…”
Section: D Aggregation For Scene Modellingmentioning
confidence: 99%
“…Detect constituent primitives. Extracting primitives, possibly only partially present, from point clouds is an important problem in surface reconstruction and reverse engineering [3,24,47,51]. Since CSDFs consist of combinations of primitives, one could detect a complete object by its constituent parts, in a similar way as how a set of 2D image descriptors on a 3D object can enable recognizing a particular object and its pose.…”
Section: Use In Object Detection Methodsmentioning
confidence: 99%
“…9), it is often a good approximation close to the surface [26]. Other implementations of the set operations have been derived (see [24,23]); these aim to strike a balance between accurately approximating the Euclidean distance and being differentiable everywhere ( Fig. 10).…”
Section: Modelling Scenesmentioning
confidence: 99%
See 1 more Smart Citation
“…The computational complexity and the respective solutions have been studied by numerous authors, as reported in [38]. For the sake of better understanding, the following articles can be noted that show the computational details regarding raster to vector graphics conversion [39][40][41], sketch processing [42][43][44], data registration [9,[45][46][47], noise removal [48,49], data reduction [50,51], curve-based surface reconstruction [42,[52][53][54][55][56][57][58], polygon-based surface reconstruction [59][60][61][62][63], and direct slicing [64][65][66][67][68].…”
Section: Introductionmentioning
confidence: 99%